2012
DOI: 10.1002/cbic.201100649
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Sialome during Zebrafish Development with Copper‐Free Click Chemistry

Abstract: The sialome comprises sialylated glycoproteins and glycolipids that play essential roles in cell–cell communication. Using azide‐modified molecular precursors of sialic acids and copper‐free click chemistry, we visualized the spatiotemporal dynamics of the sialome in live zebrafish embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 31 publications
2
67
0
2
Order By: Relevance
“…In particular, exploiting the cellular metabolism of an organism with azide-modified sugars has demonstrated a variety of experimental opportunities both for N-linked [32] and O-linked glycans [57,58]. Furthermore, the ability to provide real-time pulse-chase observations in living organisms such as the zebrafish [31,33,34] has been possible. Recent studies have also demonstrated the characterization of glycopeptides at the proteome level using bioorthogonal sugar residues [37,38].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, exploiting the cellular metabolism of an organism with azide-modified sugars has demonstrated a variety of experimental opportunities both for N-linked [32] and O-linked glycans [57,58]. Furthermore, the ability to provide real-time pulse-chase observations in living organisms such as the zebrafish [31,33,34] has been possible. Recent studies have also demonstrated the characterization of glycopeptides at the proteome level using bioorthogonal sugar residues [37,38].…”
Section: Resultsmentioning
confidence: 98%
“…Examples include bacterial cell surface labeling of using copper(I)-catalyzed [3+2] cycloaddition [28] and site-specific insertion of a bioorthogonal amino acid into a protein sequence [29]. Bertozzi et al [30] were the first to use copper-free click chemistry to link a fluorescent label to a bioorthogonal azido group incorporated metabolically onto protein glycans, and this methodology was subsequently used in many imaging studies (e.g., [31][32][33][34]). The sialic acid pathway is of most interest due to many of the aforementioned properties regarding its role in mAbs.…”
Section: Introductionmentioning
confidence: 98%
“…Then, ca . 1.0 × 10 6 cells were harvested from each culture, washed, and treated with 2 M acetic acid at 80 °C for 2 h to release sialic acids from cells, a condition that was employed to hydorlyze sialic acids in a number of literature reports 22,24,28,29 and therefore was not further optimized. This was followed by lyophilization and reaction with excessive DMB at 50 °C for 3 h. 29 After the reaction mixtures were filtered off through a 0.22 µm film, they were subjected to analysis by RP-HPLC using gradient mixtures of water and acetonitrile containing 0.1% TFA as eluents.…”
Section: Resultsmentioning
confidence: 99%
“…2 Metabolic glycan labelling has been a powerful tool for labelling cell surface glycans in vitro and in vivo. [7][8][9][10][11] In this method, cells are fed with a non-natural monosaccharide carrying a small, inert chemical reporter group. This monosaccharide is then internalised by the cells and accepted by the biosynthetic machinery of glycoprotein synthesis in the Golgi and Endoplasmic Reticulum (ER).…”
Section: Introductionmentioning
confidence: 99%